"Falling through the cracks"; Stakeholders' views around the concept and diagnosis of mild cognitive impairment and their understanding of dementia prevention. (21st July 2020) - Poppe, Michaela; Mansour, Hassan; Rapaport, Penny; Palomo, Marina; Burton, Alexandra; Morgan‐Trimmer, Sarah; Carter, Christine; Roche, Moïse; Higgs, Paul; Walker, Zuzana; Aguirre, Elisa; Bass, Nicholas; et al.
Abstract : Objectives: Many people live with an awareness of mild cognitive changes that increase their dementia risk. Previous authors describe the uncertainties of this liminal state, between cognitive health and dementia, where being "at risk" can itself be an illness. We ask how services respond to people with memory concerns currently, and how a future, effective and inclusive dementia prevention intervention might be structured for people with memory concerns. Methods/Design: We conducted qualitative interviews with 18 people aged 60+ years with subjective or objective memory problems, six family members, 10 health and social care professionals and 11 third sector workers. Interviews were audio‐recorded, transcribed and analysed using an inductive thematic approach. Results: Three main themes were identified: (1) acknowledging the liminal state, compounded by current, discordant health service responses: medicalising memory concerns yet situating responsibilities for their management with patients and families; (2) enabling change in challenging contexts of physical and cognitive frailty and social disengagement and (3) building on existing values, cultures and routines. Conclusions: Effective dementia prevention must empower individuals to make lifestyle changes within challenging contexts. Programmes must be evidence based yet sufficiently flexible to allow new activities to be fitted into people's current lives; and mindful of the risks of pathologising memory concerns. Most current memory services are neither commissioned, financially or clinically resourced to support people with memory concerns without dementia. Effective, large scale dementia prevention will require a broad societal response.